Trapped on the island: the politics of race and belonging in Jazīrat al-Maghrib. Issue 5 (3rd September 2019) - Alexander, Isabella
ABSTRACT: Drawing on ethnographic engagement with Moroccans and sub-Saharan Africans from varying socioeconomic positions this article interrogates how notions of race and belonging – or blackness and nationhood – are changing as Morocco transitions into a new destination country for migrants, refugees, and asylum seekers. Examining Jazīrat al-Maghrib as an historic and contemporary crossroads striving to maintain control over its physical and symbolic borders, the trope of island-ness emerges. Rising violence against Morocco's expanding sub-Saharan population is examined through collected narratives of citizens, migrants, and governmental officials and analyses of Moroccan popular media, revealing the racial dimensions of new political categorizations. The dangerous conflation of race, class, and presumed 'illegality' affects not only the most vulnerable, but all who could be racially categorised as non-citizen subjects. This article reveals the concrete effects that shifting sociopolitical landscapes have on Moroccans who identify as black and elite sub-Saharans who identify as part of Morocco's diverse and well-established university programme, contending that as political entanglements between Morocco and surrounding regions expand, so too does the desire for a distinctly Moroccan identity, ensuring a continuation of the historic Jazīrat al-Maghrib .